Предмет: Алгебра,
автор: алгебра
x^4-25x^2+60x-36=0
Ответы
Автор ответа:
0
x³(x - 2) + 2x²(x - 2) - 21x(x - 2) + 18(x - 2) = 0
(x - 2)*(x³ + 2x² - 21x + 18) = 0
(x - 2) *(x²(x - 1) + 3x(x - 1) - 18(x - 1)) = 0
(x - 2)*(x - 1)*(x² + 3x - 18) = 0
(x - 2)*(x - 1)*(x(x - 3) + 6(x - 3)) = 0
(x - 2)*(x - 1)*(x - 3)*(x + 6) = 0
x - 2 = 0
x = 2
x - 1 = 0
x = 1
x - 3 = 0
x = 3
x + 6 = 0
x = - 6
(x - 2)*(x³ + 2x² - 21x + 18) = 0
(x - 2) *(x²(x - 1) + 3x(x - 1) - 18(x - 1)) = 0
(x - 2)*(x - 1)*(x² + 3x - 18) = 0
(x - 2)*(x - 1)*(x(x - 3) + 6(x - 3)) = 0
(x - 2)*(x - 1)*(x - 3)*(x + 6) = 0
x - 2 = 0
x = 2
x - 1 = 0
x = 1
x - 3 = 0
x = 3
x + 6 = 0
x = - 6
Интересные вопросы
Предмет: Математика,
автор: isenkoila232
Предмет: Английский язык,
автор: liza39353
Предмет: Математика,
автор: lllllvzgt
Предмет: Математика,
автор: anastasiya